Underground Space and Climate Synergy Wind–Heat Environmental Response in Cold Zones - Lufeng Nie; Heng Liu; Jiuxin Wang; Shuai Tong; Xiang Ji (Buildings)
Underground spaces offer significant potential for sustainable urban development, particularly in cold climate regions where surface thermal fluctuations are extreme. However, optimizing the wind–heat environmental performance of such spaces remains insufficiently explored, especially in relation to spatial morphology. This study addresses this gap by investigating how underground spatial configurations influence thermal comfort and ventilation efficiency. Six representative spatial prototypes—fully enclosed, single-side open, double-side open, central atrium, wind tower, and earth kiln—were constructed based on common underground design typologies. Computational fluid dynamics (CFD) simulations were conducted to evaluate airflow patterns and thermal responses under winter and summer conditions, incorporating relevant geotechnical properties into the boundary setup. The results indicate that deeper burial depths enhance thermal stability, while central atrium and wind tower prototypes offer the most balanced performance in both ventilation and heat regulation. These findings provide valuable design guidance for climate-responsive underground developments and contribute to the interdisciplinary integration of building physics, spatial design, and geotechnical engineering.